Effect of seedbed preparation method and mulch on soil physical properties and yield of cowpea in a rice fallow of an inland valley swamp - Hulugalle, N.R.; Palada, M.C. (1990)
The effects of three seedbed preparation methods: mounds, minimum (handhoe) tillage and zero tillage; and two residue management methods: application of 4 Mg ha- ' of rice straw mulch and no mulch on soil physical properties and yield of cowpea ( Vigna unguiculata (L.) Walp.) were studied in a rice fallow of an inland valley swamp in central Nigeria during the dry seasons of 1988 and 1989. Soil physical properties measured were particle size distribution, bulk density, soil water retention, penetrometer resistance, pore size distribution, soil temperature and wetness. In general, soil compaction was such that zero tillage >> minimum tillage = mounds. The proportion of macropores in the 0-0.05 m depth was 18%, 35.2% and 42.0%, with zero tillage, minimum tillage and mounds, respectively. Diurnal soil temperatures and soil wetness were highest and lowest, respectively, on mounds, and lowest and highest, respectively, with zero tillage. Mulching had no effect on compaction but decreased diurnal soil temperature and increased wetness. The combination of zero tillage and mulch resulted in a wet, cool and compacted seedbed, whereas the warmest, driest and most porous seedbed was the bare mound. Grain yield of cowpea was not significantly affected by seedbed preparation method. Seedbed preparation methods which increase porosity and are not labour-intensive (e.g. minimum tillage) are, therefore, more appropriate for cowpea production in inland valley swamps. Mulching was effective in increasing yield, only when rainfall occurred prior to the onset of reproductive growth in cowpea such that yield was increased by 36% in 1988, but not in 1989. However, rainfall analyses indicate that moderate amounts of rainfall are likely to occur during the latter part of the dry season when reproductive growth of cowpea takes place. The least risky and hence, most appropriate soil management system for dry-season cowpea production in rice fallows of inland valley swamps is, therefore, a combination of minimum tillage and mulch.